2004
DOI: 10.1016/j.otohns.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Genial Bone Advancement Trephine System in Conjunction with Uvulopalatopharyngoplasty in the Multilevel Management of Obstructive Sleep Apnea

Abstract: The GBAT system performed in conjunction with UPPP can produce significant reductions in RDI and AI while improving the oxygen desaturation and enlarging the posterior airway space. The effective cure rates using the GBAT system are in agreement with previous reports in the literature using various GGA techniques. The GBAT may have some advantages in terms of simplicity and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…7,10 Some authors have defined surgical success or cure after UPPP as a 50% reduction in the AHI, whereas others combine this criterion with an absolute AHI of 20 or less. [11][12][13][14] Unfortunately, use of these criteria means that successfully treated patients may still have mild to moderate residual OSA. Increasing evidence shows that, when treating OSA, reducing the AHI to less than 5 is necessary to improve health care-related outcome measures, such as hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…7,10 Some authors have defined surgical success or cure after UPPP as a 50% reduction in the AHI, whereas others combine this criterion with an absolute AHI of 20 or less. [11][12][13][14] Unfortunately, use of these criteria means that successfully treated patients may still have mild to moderate residual OSA. Increasing evidence shows that, when treating OSA, reducing the AHI to less than 5 is necessary to improve health care-related outcome measures, such as hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…There is no data on the eVectiveness of GA as an independent treatment modality. The known risks of GA are long lasting numbness of the lower central incisors, exposure of plates and screws and Xoor of mouth hematomas [28]. MMA is probably the most successful operation for OSAS, but its morbidity is considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Genioglossal advancement, radiofrequency ablation of the tongue, partial midline glossectomy, lingual tonsillectomy are all surgical options that are aimed at improving oropharyngeal and hypopharyngeal obstruction with varying degrees of reported success. [82][83][84][85][86][87] Rapid maxillary expansion devices have been described in prepubertal children in an effort to widen the hard palate and enlarge the nasal cavity. Villa and colleagues 88,89 reported that, in 14 children, a mean expansion of 3.7 mm for the intercanine distance and 5.0 mm for the interpremolar distance led to an improvement in AHI from 5.8 to 1.5 events per hour, a reduction in snoring, and a reduction in daytime symptoms; this improvement was found to be persistent at 24-month follow-up PSG.…”
Section: Persistent Osasmentioning
confidence: 99%